Retained and forgotten intrauterine contraceptive devices: a case series from Kasturba Hospital, Delhi - Sinha, Maruti; Rani, Rekha; Gupta, Kavita; Gaur, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Intrauterine contraceptive devices (IUCDs) are widely used for long-acting reversible contraception. Rarely, devices may be retained, forgotten, or only discovered incidentally years later, presenting diagnostic and management challenges. We report four women who presented to the outpatient department of Kasturba Hospital, Delhi with retained or missing IUCDs. Presentations ranged from symptomatic postmenopausal bleeding and pelvic pain to incidental discovery in surgical specimens. Imaging and removal strategies varied according to clinical scenario. These cases underscore the importance of thorough history, targeted imaging, documentation of IUCD insertion, and patient education to prevent prolonged unnoticed retention. They highlight diagnostic pitfalls and management dilemmas in both symptomatic and asymptomatic retained devices.